2022
DOI: 10.1108/jhti-08-2021-0198
|View full text |Cite
|
Sign up to set email alerts
|

Sharing economy in the new hospitality: consumer perspective

Abstract: Purpose The aim of the paper is to assist hospitality business, operating in a sharing economy model and responding to coronavirus disease-2019 (COVID-19) crisis. It is argued that the creation of a strategy to face COVID-19 crisis should be focussed on what the guests valued most. The paper focusses on the Airbnb service, which is the leading platform in accommodation inside the sharing economy, to explore the consumer profile and analyse its motivations to use hospitality service, based on socio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…However, it seems reasonable to assume that the overall effects of TPB constructs are influenced by two elements. First, our data were collected during the COVID‐19 pandemic (in July 2020) implying that attitude towards CC, social pressure to engage, perceived difficulty that P2P sharing among strangers requires as well as willingness to participate in such sharing were all mostly negatively influenced by health and safety concerns—for example, difficulties in maintaining physical distancing and hygiene standards (Alharthi et al, 2021; Hossain, 2020; Julião et al, 2022). The second element possibly influencing the effect of TPB constructs is of methodological nature.…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems reasonable to assume that the overall effects of TPB constructs are influenced by two elements. First, our data were collected during the COVID‐19 pandemic (in July 2020) implying that attitude towards CC, social pressure to engage, perceived difficulty that P2P sharing among strangers requires as well as willingness to participate in such sharing were all mostly negatively influenced by health and safety concerns—for example, difficulties in maintaining physical distancing and hygiene standards (Alharthi et al, 2021; Hossain, 2020; Julião et al, 2022). The second element possibly influencing the effect of TPB constructs is of methodological nature.…”
Section: Discussionmentioning
confidence: 99%
“…The customers preferred well-established restaurant chains because of their high hygiene and safety standards. Julião et al (2022) examined the impact of socio-demographic factors on consumers' intention to use Airbnb services. The study also found that almost 80% of visitors are reluctant to stay in a room with strangers post-COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…The main highlights of the contributions of this special issue are summarized as follows. In the first article, titled “Sharing economy in the new hospitality: consumer perspective”, Julião et al . (2023) attempt to highlight how the hospitality businesses operate in a shared economy model when responding to the COVID-19 crisis.…”
Section: Exploring Tourism and Hospitality Economics At Times Of Crisismentioning
confidence: 99%